A general framework for risk consistent seismic design. - Hadjian, Asadour H.
The extensive damage sustained in recent earthquakes has highlighted the need to extend the focus of seismic design from just life safety to damage contol and functionality; and, as a corollary , to the need of analysis and design procedures that would reliably predict these additional performance expectations under several ground motion scenarios. Performance based design has been promoted as the solution. Performance based design is simply a strategy for multiple designs for pairs of specific ground motion intensities and damage states. In general, four specific ground motion exceedance levels and four specific performance limit states are considered. Since for earthquake risk management the real issues are risk and reliability, this strategy is not a sufficient basis for making informed decisions. Earthquake risk management needs information regarding the failure probability of structures for any pre-selected limit state under all possible ground motions. This paper establishes the basis and methods for a risk consistent design. Stakeholders are divided into two groups : those that have a responsibility for public health and safety, and those primarily focused on mitigating economic consequences. Public health and safety is not restricted herein to life safety or collapse prevention performances. In general, public health and safety establish minimum requirements, which are mandated by jurisdictional authorities. The other stakeholders can only select to exceed these minimum requirements. Design decisions are separated into technical solutions by engineers and risk management by stakeholders. Stakeholders have the responsibility for making risk decisions. The responsibility of the engineer is to deliver these expectations using appropriate methods of analysis, design and construction.
Keywords: Performance based design; Earthquake engineering; Earthquake risk; Risk management; Failure probability; Structural reliability